Difference of pro-health behaviors among the inhabitants of Ghana - Zieliński, Ewa; Sas, Katarzyna; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The diversity of behaviors, including pro-health ones, in developing countries is a major health, social and economic problem. Especially it affects the developing countries of Africa. In every culture, health is perceived differently. Inhabitants of different continents use different patterns of behavior, values, norms and cultural habits. The approach to health in individual cultures and social groups is the result of separate views and aspirations and from belief systems.Health indicators in Ghana are systematically improving. For example, the estimated life expectancy for people borned in 2015 was 61 years for men and 64 years for women. These indicators have been systematically growing for several dozen years thanks to the reduction of mortality caused by the medical development, improvement of hygienic and sanitary conditions, increase in the living standard, improvement of nutritional status and common protective vaccinations used in order to reduce the epidemic. Optimistic is the fact that life expectancy in health is 54 years. This is one of the best results in the sub-Saharan Africa region [1].Despite a significant improvement in the majority of health indicators, Ghana continues to face numerous prevention and health care problems. During the research projects carried out in Ghana, numerous observations have been made in this area. For example, the state of knowledge about pro-health behaviors among the residents of Ghana has been assessed. Even the preliminary observation before the preparation of the publication indicated the problem of inadequate pro-health behaviors preferred among the inhabitants of Ghana.